Ubiquitous Notification Mechanism to Provide User Awareness - López Herrera, Gustavo (2016)
Awareness could be defined as the knowledge that the user has of a particular activity, either individual or collaborative. Good awareness mechanisms provide information to the user at the right time so that s/he can know what is required for her/him to do before s/he is required to do it. Notification mechanisms are a key factor to provide awareness. Ubiquitous technologies can change the paradigm in which notifications are delivered to users. This paper describes the concept and characteristics of awareness, and how researchers have applied different notification mechanisms to provide it. With the lessons learned from 4 project implementations, we propose a service-based plug-and-play framework that models different notification mechanisms that could be used to provide user awareness.